Effects of mangosteen peel extract combined with demineralized freeze-dried bovine bone xenograft on osteocalcin, collagen 1, and osteoblast as alveolar bone regeneration in socket preservation - Utari Kresnoadi; Tika Raharjo; Rostiny Rostiny (Wolters Kluwer Medknow Publications, 2018)
Background: Tooth extraction will provoke changes in alveolar bone morphology and dimensions. Postextraction bone resorption can lead to significant problems for restorative dentistry. Therefore, the extracted tooth socket needs to be preserved to reduce alveolar ridge bone resorption. This research aimed to analyze the expression and levels of osteocalcin, collagen 1, and osteoblasts in extracted tooth sockets filled with a combination of mangosteen peel extract and demineralized freeze-dried bovine bone xenograft (DFDBBX). Material and Methods: Fifty-six Cavia cobaya, whose lower left incisors had been extracted, were divided into eight groups according to the substance used to fill their sockets on days 7 and 30, Poly ethylene glycol, DFDBBX, mangosteen peel extract, or a combination of mangosteen peel extract and DFDBBX. This research was conducted in several stages; the application of mangosteen peel extract combined with graft material was performed as the form of tooth extraction socket preservation. The C. cobaya rats were subsequently examined by immunohistochemical methods to measure osteocalcin and collagen 1 expressions, whereas histological examination was conducted to calculate the number of osteoblasts in accordance with the duration of the research. Results: On days 7 and 30, the group treated with a combination of DFDBBX and mangosteen peel extract which had the highest expression and levels of osteocalcin, collagen 1, and osteoblasts. Conclusion: The administration of mangosteen peel extract combined with DFDBBX as a means of tooth extraction socket preservation can increase osteocalcin and collagen 1 expression. Consequently, osteoblasts as a means of alveolar bone regeneration will increase in number.